Reposition of Bachelor of Social Studies Education as a Support of The Nation's Character in Facing The Society 5.0 Era - Yusuf Falaq (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
This article is the result of thinking about the repositioning of social studies education graduates as the pillars of the nation's character in facing the era of Society 5.0. In the national education system, social studies education is an integrative part that is realized by preparing human resources, curriculum, and learning, especially at the elementary and secondary education levels. Social studies education graduates' functions and roles in achieving national education goals are designed and implemented as a form of realization. A frame of mind that understands that social studies education reflects the character of a civilized nation. National character is essential during the Era of Society 5.0, which requires the public to control and balance the capabilities of artificial intelligence and social intelligence to solve all kinds of national problems. Society 5.0 illustrates that everything can be moved and connected through data to overcome social problems. The position of the social studies education graduate is very strategic because it can balance the two things. Social studies education graduates have challenges presenting knowledge and skills of critical, constructive and innovative thinking by staying within the emotional, social, and spiritual intelligence firmly entrenched as mandated in Pancasila and the 1945 Constitution.